PENGARUH PELAKSANAAN CORPORATE SOCIAL RESPONSIBILITY (CSR) PT RAPP TERHADAP SOSIAL EKONOMI MASYARAKAT DESA KIAP JAYA KECAMATAN BANDAR SEIKIJANG - Suryani Suryani; Almasdi Syahza; Riadi Armas (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACTPT RAPP is committed to be a part of the County and the community actively involved in the development of economic, social, and cultural communities. In determining the program, RAPP engage in dialogue with the community and try to see more prudent pattern and the concept of CSR is more beneficial and useful to society and to implement in society. Formulation of the problem of this research is how the effect of implementation of Corporate Social Responsibility PT RAPP against Kiap Jaya villagers Bandar Seikijang subdistrict. The purpose of this study is to investigate and understand the effect of the implementation of Corporate Social Responsibility PT RAPP against Kiap Jaya villagers Bandar Seikijang subdistrict. Data collection techniques used observation, interviews, questionnaires and documentation. Analysis using univariate and bivariate analysis. The variables of this research is the corporate social reponsibility which is a variable X. While the socio-economic variables are as variable Y. From the observations and data processing , it is known that the implementation of corporate social responsibility (CSR) PT RAPP has a significant effect on the socioeconomic village Kiap Seikijang Bandar Jaya subdistrict . It is known from the results of Chi Square test of respondents ' perceptions about the effect of the implementation of corporate social responsibility ( CSR ) PT RAPP against villagers socioeconomic Kiap Bandar Jaya subdistrict Seikijang shows the results of Chi count 37.552 , while Chi table shows the results of 9.488 . Therefore Chi count > of Chi table , it can be concluded that the implementation of corporate social responsibility ( CSR ) PT RAPP has a significant impact on rural communities socioeconomic Kiap Seikijang Bandar Jaya subdistrict.Keywords : Corporate Social Responsibility, Socioeconomic